Childhood in the Philosophy of Maurice Merleau-Ponty. The barbarian thinking of children as an expression of the world of life - Buffone, Jesica Estefanía (2019)
In this paper an analysis will be conducted on some of the works of Maurice MerleauPonty, in which the phenomenologist provides a description of childhood or where the child image will report any relevant aspect within his theory. The description of the child as a place inhabited by many places, as a primary silence or asthat unspeakable, shows us the childhood as the opening of a new field of experience, as the institution of a new sense. Childhood will not only be a methodological interest object in his psychology studies, but also that primal going-forward of experience, the mere potentiality yet not thrown (or rather, not yet been thrown) in the world where everything will, necessarily, have sense.